Hepatitis B virus genotyping among chronic hepatitis B patients with resistance to treatment with lamivudine in the City of Ribeirão Preto, State of São Paulo Genotipagem do vírus da hepatite B de pacientes crônicos com resistência ao tratamento com lamivudina na Cidade de Ribeirão Preto, Estado de São Paulo - Rodrigo Haddad; Ana de Lourdes Candolo Martinelli; Sérgio Akira Uyemura; Jonny Yokosawa (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Lamivudine is a nucleoside analogue that is used clinically for treating chronic hepatitis B infection. However, the main problem with prolonged use of lamivudine is the development of viral resistance to the treatment. Mutations in the YMDD motif of the hepatitis B virus DNA polymerase gene have been associated with resistance to drug therapy. So far, there have not been many studies in Brazil reporting on genotype-dependent development of resistance to lamivudine. Thus, the aim of the present study was to determine the possible correlation between a certain genotype and increased development of resistance to lamivudine among chronic hepatitis B patients. METHODS: HBV DNA in samples from 50 patients under lamivudine treatment was amplified by means of conventional PCR. Samples were collected at Hospital das Clínicas, FMRP-USP. The products were then sequenced and phylogenetic analysis was performed. RESULTS: Phylogenetic analysis revealed that 29 (58%) patients were infected with genotype D, 20 (40%) with genotype A and one (2%) with genotype F. Mutations in the YMDD motif occurred in 20% of the patients with genotype A and 27.6% of the patients with genotype D. CONCLUSIONS: Despite the small number of samples, our results indicated that mutations in the YMDD motif were 1.38 times more frequent in genotype D than in genotype A. INTRODUÇÃO: Lamivudina é um análogo de nucleosídeo clinicamente utilizado para o tratamento da infecção crônica pela hepatite B. Entretanto, o principal problema do uso prolongado da lamivudina é o desenvolvimento de resistência viral ao tratamento. Mutações no motivo YMDD no gene da DNA polimerase do vírus da hepatite B estão associados com a resistência a terapia medicamentosa. Até o presente momento, não há muitos estudos no Brasil que descrevem o desenvolvimento genótipo-dependente da resistência à lamivudina. Assim, o intuito do trabalho aqui descrito foi determinar a possível correlação entre um determinado genótipo e o desenvolvimento aumentado da resistência à ...